Phase I Safety Study of Ranolazine in Pulmonary Arterial Hypertension. (1st December 2015) - Gomberg‐Maitland, Mardi; Schilz, Robert; Mediratta, Anuj; Addetia, Karima; Coslet, Sandra; Thomeas, Vasiliki; Gillies, Hunter; Oudiz, Ronald J.
Abstract : Pulmonary arterial hypertension (PAH) causes right ventricular ischemia, dysfunction, and failure. PAH patients may benefit from antianginal agents based on a shared pathophysiology with left ventricular ischemia. A single‐center, randomized, placebo‐controlled trial (1 : 1) to assess the acute vasoreactivity and safety of ranolazine in PAH was conducted. Plasma samples for pharmacokinetic (PK) studies were drawn during hemodynamic measurements at 0, 60, 90, 120, 240, and 360 minutes from a Swan‐Ganz catheter. All patients received 500‐mg doses, uptitrated to 1, 000 mg at week 4, monthly evaluations, and a complete objective assessment after 12 weeks, followed by an open‐label extension. Thirteen patients were randomized and 12 enrolled (6 ranolazine, 6 placebo). All patients completed the acute phase; 10 completed the 12‐week study. There were no acute changes in invasive hemodynamics. At 12 weeks ranolazine was well tolerated. Only 1 of the 5 patients on ranolazine had a serum concentration considered to be in the therapeutic range. Two serious adverse events required early withdrawal (both in the ranolazine group); gastrointestinal complaints were the most common adverse event. Efficacy measures did not demonstrate any differences between treatment groups. During the open‐label trial, 2 additional patients reached a therapeutic concentration. Ranolazine in PAH appears safe, without acute hemodynamic effects after a 500‐mg dose. Ranolazine administrated to PAH patients receiving background PAH therapies did not consistently reach therapeutic levels. Future studies should first perform PK analysis in PAH patients receiving PAH therapies and explore the safety and tolerability of the higher doses perhaps necessary to achieve therapeutic levels in PAH patients. (Trial registration: Clinicaltrials.gov identifier NCT01757808.)